Motility characteristics of spermatozoa in cod (Gadus morhua) and hake (Merluccius merluccius) - Cosson, Jacky; Groison, Anne-laure; Suquet, Marc; Fauvel, Christian (Société Française d'Ichtyologie, 2008)
As in many marine fish, motility is triggered by osmotic pressure (OP) in cod and hake spermatozoa and motility ranges several minutes with a high velocity (above 50 mu m/s) period restricted to 100 s. A decrease in the flagellar beat frequency (BF) is partly responsible of this briefness. Detailed observations of the flagella during the motility period showed: 1) sea water provokes OP damages (blebs) which impair the correct wave propagation 2) waves become restricted to the proximal flagellum and tip becomes devoid of wave 3) the wave amplitude decreases. The combination of these factors drastically limits to the earliest period of motility the ability for spermatozoa to efficiently progress towards egg for fertilization.